The Impact of Sostac's Digital Marketing Planning Strategy on Marketing Performance Through Competitive Advantage - Suharyati Suharyati; Tati Handayani; Nobelson Nobelson (Research Synergy Foundation, 2023)
The majority of MSMEs in the Sukmajaya sub-district, Depok, are engaged in the culinary field, totaling 771 MSMEs out of a total of 2,835 MSMEs. The decline in the number of MSMEs in 2020 due to the Covid-19 pandemic has made it difficult for MSMEs to market their products. On the other hand, during this period, SMEs emerged with digital innovation. Digital marketing planning is necessary for MSMEs in running their business to create a competitive advantage and improve marketing performance. MSMEs that do not implement digital marketing in running their business will be left behind and lose customers because customer buying behavior has changed towards digital. This research is quantitative descriptive research using the SmartPLS 3.0 tool to analyze the effect of each variable. The type of data is primary data by distributing questionnaires to 125 Culinary MSME respondents in the Sukmajaya sub-district, Depok city via Google form. In this study, data analysis techniques were carried out in the form of descriptive data analysis and inferential data analysis, and hypothesis testing. The results of the study prove that digital marketing planning using the SOSTAC method has a positive and significant effect on Competitive advantage, SOSTAC Digital marketing planning has a positive and significant effect on marketing performance and Competitive advantage has a positive and significant effect on marketing performance. The results of the study show that SOSTAC Digital Marketing Planning has a positive and significant indirect relationship to marketing performance through competitive advantage, which is bigger than the direct relationship. Thus, in SOSTAC Digital Marketing Planning, to achieve marketing performance, MSME actors must first be able to create a competitive advantage.